"It Has Changed": Understanding Change in a Parenting Program in South Africa - Jenny Doubt; Rachel Bray; Heidi Loening-Voysey; Lucie Cluver; Jasmina Byrne; Divane Nzima; Barnaby King; Yulia Shenderovich; Janina Steinert; Sally Medley (Ubiquity Press, 2017)
Background Poor parenting that leads to child maltreatment during adolescence presents a major public health burden. Research from high-income countries indicates that evidence-based parenting program interventions can reduce child maltreatment. Much less is known, however, about how beneficiaries of these programs experience this process of change. Understanding the process that brings about change in child maltreatment practices is essential to understanding intervention mechanisms of change. This is particularly important given the current scale-up of parenting programs across low- and middle-income countries. Objectives This study aimed to provide insight into how caregivers and adolescents attending a parenting program in South Africa perceived changes associated with abuse reduction. Methods Semi-structured interviews were conducted with caregivers and adolescents (n = 42) after the intervention, as well as observations of sessions (n = 9) and focus group discussions (n = 240 people). Participants were adolescents between the ages of 10-18 and their primary caregiver residing in peri-urban and rural program clusters in the Eastern Cape Province of South Africa. Data were coded in Atlas.ti, and thematic content analysis was conducted. Findings Based on participant perceptions, the Sinovuyo Teen parenting program workshops catalyzed change into practice by creating an environment that was conducive to learning alternatives. It did so through prioritizing a process of mutual respect, openness, and being valued by others, giving legitimacy to a respectful reciprocity and new ways of spending time together that enabled caregivers and teenagers to shift and normalize more positive behaviors. This in turn led to reductions in physical and verbal abuse. Conclusions This study's findings may be of use to policymakers and practitioners who need to understand how parenting programs support parents and teenagers in increasing positive parenting approaches and changing potentially harmful practices. It additionally highlights the importance of assessing the experiences of both parents and teenagers attending such programs.